CRBs for direction‐of‐departure and direction‐of‐arrival estimation in collocated MIMO radar in the presence of unknown spatially coloured noise. Issue 4 (1st April 2019) - Wen, Fangqing; Zhang, Xinyu; Zhang, Zijing
Abstract : This study gives explicit closed‐form expressions of the stochastic Cramer–Rao bounds (STO‐CRBs) on direction‐of‐departure and direction‐of‐arrival estimation accuracies for collocated multiple‐input–multiple‐output (MIMO) radar with unknown spatially coloured noise. In some special cases, i.e. the CRB of direction estimation accuracy for monostatic MIMO radar, the white noise scenario is discussed. Theoretical comparisons between the STO‐CRBs and the deterministic ones are presented. Finally, these bounds are numerically compared.